Seasonal Changes in Gaelic Football Match-Play Running Performance. Issue 6 (June 2019) - Mangan, Shane; Ryan, Martin; Shovlin, Aidan; McGahan, Jason; Malone, Shane; O'Neill, Cian; Burns, Con; Collins, Kieran
Abstract : Abstract: Mangan, S, Ryan, M, Shovlin, A, McGahan, J, Malone, S, O'Neill, C, Burns, C, and Collins, K. Seasonal changes in Gaelic football match-play running performance. J Strength Cond Res 33(6): 1686–1692, 2019—Time of season influences performance in many team sports; however, the anomaly has not yet been examined with regards to elite Gaelic football. Global positioning systems (4 Hz; VX Sport, Lower Hutt, New Zealand) were used to monitor 5 elite Gaelic football teams over a period of 5 years (2012–2016). In total, 95 matches equated to 780 full player data sets. Running performance was characterized by total distance (m) and high-speed distance (≥17 km·h −1 ; m). High-speed distance was further categorized into 4 match quarters. Time of season was determined by month of the year. Time of season had a significant effect on total distance ( p ⩽ 0.001 partial η 2 = 0.148) and high-speed distance ( p ⩽ 0.001 partial η 2 = 0.105). August and September were significantly different from every other month for total distance ( p ⩽ 0.001) and high-speed distance ( p ⩽ 0.002). Month of season and match quarter had a significant interaction with high-speed distance ( p ⩽ 0.001 partial η 2 = 0.106). High-speed distances run in the fourth quarter in August (478 ± 237 m) and in September (500 ± 219 m) were higher than any other quarter in any other month. This is the first study to show that time of season influences running performance in Gaelic football. The findings have major implications for training practices in Gaelic football.